A review on systematic approach for microbial enhanced oil recovery technologies: Opportunities and challenges. (10th June 2020) - Saravanan, Anbalagan; Kumar, Ponnusamy Senthil; Vardhan, Kilaru Harsha; Jeevanantham, Sathasivam; Karishma, Suresh Babu; Yaashikaa, Ponnambalam Ragini; Vellaichamy, Parthasarathy
Abstract: Oil is an indispensable ingredient for both food and energy in most of the countries. Due to insufficient extraction process reduces the average oil recovery rate up to 30%. Enhanced oil recovery (EOR) technologies including physical, chemical and biological methods are used to regain circumvent and lasting oil caught in supply after essential and optional recuperation techniques. Microbial Enhanced Oil Recovery (MEOR) is an effective alternative method for oil recovery among other EOR methods (physical and chemical methods). Microorganisms and their by-products are the responsible factor for MEOR process. Microorganisms in the oil reservoirs enhance the recovery process by producing various metabolites such as biosurfactants, biopolymers, acids, gases, biomass, etc. through in-situ mechanism. In the present review, explains the MEOR process along with existing conventional oil recovery methods. It's also describes the production of various microbial metabolites, their financial related issues, applications of lab-to-deal with scale, different productive primers of interest and their drawbacks are addressed. In future, logical models used for the EOR process was proposed.